Development of piezoelectric scaffolds and their synergistic effects with pulsed electromagnetic fields on osteogenesis - Dong, Yibing (Nanyang Technological University, 2022)
With the worldwide bone disorders and conditions trended steeply upward, the demands for engineering bone tissue and effective bone lesion treatments have increased significantly. Key strategies for bone formation and regeneration involve the collective application of biomaterials, cells, physicomechanical and biochemical therapies to enhance osteogenesis. Since bone exhibits piezoelectric properties, electrical stimulations such as pulsed electromagnetic fields (PEMFs) and stimuli-responsive piezoelectric scaffolds have been investigated in separate studies to evaluate their efficacy in supporting osteogenesis. However, the current understanding of cells and biological systems responding under the combined influence of PEMF and piezoelectric properties in scaffolds is still lacking. Therefore, in this study, we aimed to fabricate a piezoelectric scaffold based on clinically successful polycaprolactone-tricalcium phosphate (PCLTCP) scaffolds and further evaluate and understand the osteogenic potential of the piezoelectric scaffold in combination with PEMF in evidence-based pre-clinical studies. It is hypothesized that piezoelectric scaffolds could be fabricated by functionalization of PCLTCP films with a polyvinylidene fluoride (PVDF) coating that is self-polarized by a modified breath-figure technique. It is also hypothesized that the piezoelectric scaffolds, with PEMF stimulation, could evoke a positive cellular response and provide electrically augmented osteogenesis in vitro and in vivo. To validate the hypotheses, four specific aims were identified, and the scope of the experiments was designed. Specifically, the fabrication method for piezoelectric scaffolds using hydrogen bonding was developed at a low temperature. Piezoelectric and ferroelectric characterization demonstrated that the scaffolds with piezoelectric coefficient d33 = − 1.2 pC/N were obtained at a powder dissolution temperature of 100 °C and coating relative humidity (RH) of 56%. The developed protocol provided a versatile strategy to facilitate polarization of PVDF on the surface of complex structures and at a low temperature. Subsequently, cell-material interactions and osteoinductive properties were evaluated for PVDF-coated PCLTCP scaffolds coupled with PEMF using a pre-osteoblast cell line (MC3T3-E1) in Abstract ii vitro. DNA quantification showed that cell proliferation was significantly enhanced by PEMF as low as 0.6 mT and 50 Hz. Hydroxyapatite staining showed that cell mineralization was significantly enhanced by the incorporation of PVDF coating. Gene expression study showed that the combination of PEMF and PVDF coating promoted the expression of late osteogenic gene markers most significantly. In addition, the biocompatibility and osteogenic feasibility of PVDF-coated PCLTCP scaffolds was studied using a rat calvarial defect model in vivo. Haemotoxylin and Eosin (H&E) staining and Micro-CT imaging confirmed that PVDF-coated PCLTCP scaffolds provided guided bone regeneration (GBR) and facilitated compact bone formation. Masson’s trichrome (MT) staining showed that the incorporation of PVDF coating induced the higher fraction of mature bone formation by 63%. Lastly, the biological response and osteogenic potential of duo-stimulation by PVDF-coated PCLTCP scaffolds and PEMF were evaluated using a chicken embryo model. Egg viability could be raised by either PVDF coating or PEMF, whereas the morphometrical study of chicken embryos showed the body and vital organ growth was enhanced by the synergistic application of PVDF-coated PCLTCP scaffolds and PEMF, which indicated excellent biocompatibility in vivo. Micro-CT analysis showed bone volume was more significantly increased by PEMF stimulation (89% higher). Calcium quantification in amniotic fluid (60% higher) and H&E staining indicated the synergistic advancement of bone mineralization and bone maturity stages respectively by PEMF and PVDF. Collectively, for the first time, our study provided in-depth pre-clinical validation of the potential in a synergistic combination of PVDF-coated PCLTCP scaffolds and PEMF as a powerful strategy for electrically augmented osteogenesis. The piezoelectric response of PVDF by PEMF, which provide mechanical strain, is particularly interesting as it could deliver local mechanical stimulation by remote control of PEMF. The mechanism proposed in this study could also generate new ideas for further exploration and reinforcement of fundamental study in both material science and molecular biology.